RANCANG BANGUN PROTOTYPE ROBOT PIPE TRACKING DENGAN ELECTRIC NOSE TECHNOLOGY SEBAGAI DETEKTOR KEBOCORAN - Anindya, Citta; Fuada, Syifaul; Firmansyah, Sugeng; Lestari, Dyah (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
An industrial gas leak will cause material losses and impede the gas distribution of the company. In addition, it can also threaten human lives if the gas leaked is of toxic and inflammable gasses. Thus, to overcome these issues, the researchers had developed an automatic gas leak detection system through this prototype. In this journal, the researchers described how to make a prototype of a robot for monitoring the gas leak. The designed robotwasof Out-Pipe Robot type anda PVC pipe was used as the real replica of the pipe. This study was conducted for three purposes: (1) Determining the design; (2) Describing themaking processand(3) Explaining theperformance test ofthe prototype of pipe tracking robotusingelectricnosetechnologyasthe gas leakdetector. The workingsystem of this pipe tracking robotis by trackingthe pipe usingthe HC-SR04 ultrasonicsensor. If the MQ-6gassensordetects the presence ofa gas leak, thegas sensorwilldetectthe gasandconvert itintovoltage. Then, the gas sensors will transmit the input voltage to the Arduino microcontroller, after which the output of the Arduino microcontroller will release the data to the LCD and display it in the form of digital figures in accordance with the level and type of the leaked gas. Besides, the buzzer will start soundingonce it detects the presence of the gas. The results of the study were: (1) The device is able to track the pipe which wasÂ Â± 10 cm in diameter, (2) The device is able to detect gas other than clean air, (3) The flashing LCD screen indicating that it detected the presence of gas, (4) The ideal distance to be maintained between the pipe and the mobile robot was 5 cm. With the ideal distance, the mobile sensors could easily track over a pipe installation without getting distracted by other objects. (5) The time reference used as the detection range was 1 minute. By doing so, the sensor will be more sensitive.Â Keywords - Arduino, Electric Nose Technology, Gas leak detector, Mobile Robot, Pipe Tracking